Evaluating Patient-Centered Outcomes in Clinical Trials of Procedural Sedation, Part 1 Efficacy: Sedation Consortium on Endpoints and Procedures for Treatment, Education, and Research Recommendations. (March 2017) - Williams, Mark R.; Ward, Denham S.; Carlson, Douglas; Cravero, Joseph; Dexter, Franklin; Lightdale, Jenifer R.; Mason, Keira P.; Miner, James; Vargo, John J.; Berkenbosch, John W.; Clark, Randall M.; Constant, Isabelle; et al.
Abstract : The Sedation Consortium on Endpoints and Procedures for Treatment, Education, and Research, established by the Analgesic, Anesthetic, and Addiction Clinical Trial Translations, Innovations, Opportunities, and Networks public–private partnership with the US Food and Drug Administration, convened a meeting of sedation experts from a variety of clinical specialties and research backgrounds with the objective of developing recommendations for procedural sedation research. Four core outcome domains were recommended for consideration in sedation clinical trials: (1) safety, (2) efficacy, (3) patient-centered and/or family-centered outcomes, and (4) efficiency. This meeting identified core outcome measures within the efficacy and patient-centered and/or family-centered domains. Safety will be addressed in a subsequent meeting, and efficiency will not be addressed at this time. These measures encompass depth and levels of sedation, proceduralist and patient satisfaction, patient recall, and degree of pain experienced. Consistent use of the recommended outcome measures will facilitate the comprehensive reporting across sedation trials, along with meaningful comparisons among studies and interventions in systematic reviews and meta-analyses. Abstract : Published ahead of print September 12, 2016.